MENGGALI NILAI-NILAI KEARIFAN LOKAL RAMPAK NAONG BRINGEN KORONG SEBAGAI SUMBER BELAJAR IPS DI KELAS IV MI AL HIDAYAH SINGKAWANG - Dewi, Elista; Fitriyadi, Slamat; Suprapto, Wasis (CV. Lafadz Jaya, 2023)
This research aims to describe the values contained in the Rampak Naong Bringen Korong philosophy in learning and knowing the use of Rampak Naong Bringen Korong philosophical values as a learning resource for class IV social studies at MI Al Hidayah. The type of research used is qualitative research with an ethnoscience research design. This research was carried out at MI Al Hidayah Singkawang. Data collection techniques use observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. The results of the research show that: 1) the philosophical values of Rampak Naong Bringen Korong, namely the value of togetherness, the value of balance, and the value of peace, have a huge impact on students and Indonesian local wisdom. So that they don't fade with time, the Rampak Naong Bringen Korong values in social studies learning are taught so that students can understand more about local Indonesian wisdom. 2) the use of Rampak Naong Bringen Korong values as a social studies learning resource at MI Al Hidayah, can be implemented in the social studies subjects KD 3.2 and KD 4.2 in the class IV syllabus for the even semester.